Employee Engagement: Antecedents and Consequences - Mahwash Ghafoor Chaudhry (UW Journal of Management Sciences, 2022)
Purpose: In continuously emerging environment, organization needs to gain competitive edge to stay dynamic and sometimes simply to survive. Despite the fact the technology plays a dominant role in providing a sustainable competitive advantage, the essential and significant role played by human resource and its management in the analysis of the competitive advantage cannot be overlooked. This brings the attention of the academia and researchers on investigating the value of employees to organizations by fostering employee engagement (EE). This research aims to study antecedents and consequences of EE. Design/Methodology: The research uses the quantitative research approach using survey method with analysis conducted on the responses from 150 respondents. The research focused three service sectors namely banking, education and telecommunications in the cities of Bahawalnagar, Bhawalpur, Pakpatan and Lahore. Findings: Results of the present study provides evidence of existence of a strong relationship between Job Satisfaction (JS), Reward and Recognition (R&R), Leader Membership Exchange (LMX), Employee Engagement (EE), and a negative but significant relationship between Intention to quit (I-Q), JS & EE, but none between Organizational Citizenship Behavior (OCB) and JS. Managerial Implications: This research offers better understanding of EE in organizational context and in relation to the variables considered highly significant in relation to EE as suggested by literature. This will help organizations to improve EE to enhance overall organizational performance. The limitations are that the OCB organizational and OCB Individual was not differentiated, improved response resulted using translated questionnaire and cross sectional study by using different techniques.